Imaging of Mixed and Radiopaque Jaw Lesions - Vanhoenacker, Filip M.; Bosmans, Frederik; Vanhoenacker, Charlotte; Bernaerts, Anja (Seminars in Musculoskeletal Radiology, 2020)
Radiopaque lesions and lesions of mixed density are less frequent than radiolucent lesions of the jawbones. They comprise a spectrum of odontogenic and non-odontogenic lesions. The latter group includes inherited and developmental disorders, osteomyelitis, and benign and malignant primary bone tumors and metastases. Most odontogenic radiopaque or mixed lesions are either related to the apex or more rarely to the crown of the tooth, although there are exceptions to this rule. Some lesions, such as a torus mandibularis and torus palatinus, have a characteristic location, whereas others show no relationship to the dentition. This article describes the most characteristic and prevalent radiopaque and mixed lesions of the jaws and their imaging characteristics. Paget's disease, fibrous dysplasia, and rare sclerotic bone diseases of the maxillofacial bones are discussed elsewhere in this issue. Careful correlation of clinical presentation, panoramic radiographs, cone beam computed tomography, and histopathology are the cornerstones for appropriate lesion characterization.
Keywords: jaws; tumor and tumor-like lesions; increased bone density; cone beam computed tomography; imaging